2022
DOI: 10.1186/s12889-022-13680-1
|View full text |Cite
|
Sign up to set email alerts
|

Speaking COVID-19: supporting COVID-19 communication and engagement efforts with people from culturally and linguistically diverse communities

Abstract: Background Since the emergence of COVID-19, issues have been raised regarding the approach used to engage with Culturally and Linguistically Diverse (CaLD) communities during this public health crisis. This study aimed to understand the factors impacting communication and engagement efforts during the COVID-19 pandemic from the perspective of crucial CaLD community stakeholders and opinion leaders. Methods Forty-six semi-structured telephone interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…In fact, some of our research team assisted participants to book vaccination appointments on their smartphones after the focus groups or provide further information to partners who waited in the car park to speak with them. It is not just our participants who struggled with the online booking system: Seale et al 29 describe a ‘digital divide’ in which those without access to the internet and have low English proficiency are disadvantaged in their ability to access COVID‐19 vaccines, and Biddle et al 27 identified that Australians who completed the 2016 census on paper rather than online had a lower probability of vaccination, suggesting that individuals with lower digital literacy may experience more barriers to vaccination. Booking systems must be accessible to varying levels of digital literacy and English proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, some of our research team assisted participants to book vaccination appointments on their smartphones after the focus groups or provide further information to partners who waited in the car park to speak with them. It is not just our participants who struggled with the online booking system: Seale et al 29 describe a ‘digital divide’ in which those without access to the internet and have low English proficiency are disadvantaged in their ability to access COVID‐19 vaccines, and Biddle et al 27 identified that Australians who completed the 2016 census on paper rather than online had a lower probability of vaccination, suggesting that individuals with lower digital literacy may experience more barriers to vaccination. Booking systems must be accessible to varying levels of digital literacy and English proficiency.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In eastern Australia, Mahimbo et al 9 identified that CALD communities are eager for community engagement, and for their leaders to champion the vaccine. Seale et al 29 identified that while some CALD organizations in Australia were updating local CALD leaders on relevant COVID‐19 information to share with their community, there was a lack of training in how to do so. Training influential community leaders can occur over a relatively short period of time: a COVID‐19 information and support programme was offered in the United States to CALD community leaders which involved 1‐hour conference calls twice a week (we acknowledge that this is then reliant on the leaders having a decent level of computer literacy.)…”
Section: Implications For Policy and Practicementioning
confidence: 99%
See 3 more Smart Citations